(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Purpose of this study is to research the floating type cylindrical hologram that can also be embodied in the outdoor. This study identifies the floating hologram and its type, and researches the applied form design and realization type based on floating hologram realization type. For the manufacturing of miniature hologram, the floating mirror is installed in cylinder to embody new hologram type out of existing hologram. For the design of cylinder, the polarizing filter is used to minimize the diffracted reflection, and air intake device, the fan is installed to minimize the problem of heat and humidity. The study was able to check if realistic content that can be installed in outdoor space is embodied by researching how to minimize the problem of outdoor cylinder floating hologram.